Pemikiran Manajemen Pendidikan Islam pada Masa Khulafaurasyidin - Rohadi; Muhammad Syaifuddin (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to analyze the period of Islamic Education Management Thought during the Khulafaurasyidin Period. Data collection with documentation. Analysis with SLR. Mecca, with Muadz bin Jabal radhīyallāhu 'anhu as the first teacher who taught the Koran and fiqh. 2. Medina, whose teachers were the most popular companions of the Prophet, namely Abu Bakr, Uthman bin Affan, Ali bin Abi Talib, and other companions. 3. Basrah, the teacher was Abu Musa al-Asy'ary radhīyallāhu 'anhu who was an expert in jurisprudence and the Qur'an. 4. Kuffah, famous teachers namely Ali bin Abi Talib and Abdullah bin Mas'ud radhīyallāhu 'anhum. Abdullah bin Mas'ud is an expert on tafsir, hadith and fiqh and teaches the Koran. 5. Damascus (Syam). After Sham (Syria) became part of an Islamic country and its population was mostly Muslim, Caliph Umar then sent three teachers to that country, namely Mu'adz bin Jabal, Ubaidah, and Abu Darda' radhīyallāhu 'anhum. They taught in different places in the city of Syria, namely Abu Darda' in Damascus City, Mu'adz bin Jabal in Palestine City, and Ubaidah in Hims City.